Aesthetic Attributes of Museum Environmental Experience: A Pilot Study With Children as Visitors - Annechini, Claudia; Menardo, Elisa; Hall, Rob; Pasini, Margherita (Frontiers in Psychology, 2020)
The research project is a small pilot study of the restorative aspects of museum experience on children; these include the sense of fascination during the visit. Museum environmental awareness was a latecomer to Museum and Visitor studies but is now highly valued. No longer just the "objects" contained in the museum fascinate, but also the environment itself becomes an object of fascination. Some authors provide a clear categorization of feelings experienced by the visitor during a museum experience and suggest a framework with four categories of satisfying experience: objective, cognitive, introspective and social. In designing our study, we began with the definition of museum experience and added a fifth category of “environmental experience”. With this term we use to refer to the extent to which the physical environment in and around a museum affects visitors. Indeed, our aim is to analyze the visitor’s stream of feelings and opinions during a museum visit (specifically, the MART - Museum of Modern and Contemporary Art of Trento and Rovereto), to find a proper definition of the aesthetic elements characterizing the “environmental preference”. To do this, we referenced classical and experimental paradigms of Environmental Psychology applied to a museum context and building aesthetic researches, combining qualitative and quantitative approaches. The case study involved 41 children, 20 males and 21 females, from two primary school classes in Rovereto (Italy), the average age was 8.3 years old.